Stirling Engine and oil-free compressors - Raballand Thierry (EDP Sciences, 2021)
Refering to figure 1 [Fig.1], an oscillating « flipper » piston (1) and its associated chamber (2) are maintained without reciprocal contact. No oil is required because there is no contact and so no friction. An oscillating shaft (22) maintains the oscillating « flipper »piston (1). Around shaft (22), a twisting seal (8) allows for absolute sealing. This characteristic is important for Stirling engines and oil-free compressors. Referring to figure 4 [Fig.4], the two oscillating « flipper » pistons on the left belong to a Stirling-Franchot engine, more particularly to a Stirling-Franchot engine with two oscillating « flipper » pistons and so with two quadric crank mechanisms. The oscillating « flipper » piston on the right belongs to an oil-free compressor. The Stirling engine shaft (11), which is in alternative rotation, directly powers the oil-free compressor shaft (22). This prevents the use of a third quadric crank mechanism from shaft (33) to shaft (22). A Stirling engine connected to an oilfree compressor is useful when the fluid is precious or dangerous. A French patent was taken out on Februar 1st, 2020.